EPITHELIAL NEOPLASMS OF THE CECAL APPENDIX - Costa, Lineker Velozo; Araujo, Moisés Ederlanio Tavares de; Batista, Hermes Melo Teixeira; Nóbrega, Edgley Almeida; Araújo, Anna Clara Carvalho Curvina Costa de; Araújo, Cicera Yolanda dos Santos (Amadeus International Multidisciplinary Journal, 2018)
Cecal appendix carcinoma is characterized as an extremely rare condition and is found in only 1% of appendectomies and accounts for only 0.5% of neoplasms of the intestinal tract. The aim of the study is to discuss Appendix Carcinomatosis by presenting a case of Cecal Appendix Epithelial Neoplasm seen during the Surgery Residence. Keywords: Appendix Vermiformis, Acute Abdomen, Appendix Neoplasm.